Electronic structure and magneto-optical Kerr effect in UCuAs2: Электpонные свойства металлов и сплавов - Antonov*, V. N.; Harmon, B. N.; Horpynyuk, O.; Yaresko, A. N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2002)
The optical and magneto-optical (MO) spectra of the ternary compound UCuAs2 are investigatedtheoretically from first principles, using the fully relativistic Dirac linear-muffin-tin-orbital band structure method. The electronic structure is obtained with the local spin-density approximation(LSDA), as well as with the so-called LSDA+U approach. Better agreement between the theoreticallycalculated and the experimentally measured MO Kerr spectra is found with the LSDA+U approximation. The origin of the Kerr rotation in the compound is examined.